MIL-53(Fe)-mediated persulfate activation for the removal of pesticides-contaminated water: phytotoxicity evaluation, theoretical reactivity prediction and by-products degradation pathways - Muriel R. Affonso; Igor G.S. Oliveira; Fernando C. Gallina; Beatriz T. Marin; João P.P. Encide; Micael M. Baruch; Robson S. Souto; Renata Colombo; Kathia M. Honorio; Marcos R.V. Lanza; Willyam R.P. Barros (Chemical Engineering Journal, 2026)

Isotopic insights into the fate of atmospheric nitrogen in alpine tundra ponds with contrasting land cover and cryospheric conditions - R. Balestrini; N. Colombo; M. Freppaz; M.F. Lehmann; C. Delconte; E. Pintaldi; F. Salerno; I. Matiatos (CATENA, 2026)

Corrigendum to “Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil)” [J. Geochem. Explor. 281,107934 (2026)] - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Geochemical and isotopic signature of a rift-to-arc transition in the Neoproterozoic Adrar Souttouf Massif, Moroccan Sahara - Omar Guillou; M'hamed El Janati; Nasrrddine Youbi; Andreas Gärtner; Michel Villeneuve; João Mata; Jean-Louis Bodinier; Abdelhak Ait Lahna; Moualy Ahmed Boumehdi; Ismail Hadimi; Oussama Moutbir; Colombo Celso Gaeta Tassinari; et al. (Geochemistry, 2026)

Reducing effects of isoliquiritigenin, a naturally occurring GABAB receptor agonist, on alcohol-motivated behaviors in alcohol-preferring rats - Paola Maccioni; Laura Regonini Somenzi; Mauro A. M. Carai; Federico Corelli; Gian Luigi Gessa; Giancarlo Colombo (Psychopharmacology, 2026)
Rationale and objectives Glycyrrhiza glabra L. (Fabaceae; licorice) is a widely used medicinal herb known to exert protective effects against multiple neurological diseases. The flavonoid, isoliquiritigenin (ISL), is a main constituent of roots of Glycyrrhiza glabra . ISL has been reported to behave as a GABA B receptor agonist and exert multiple pharmacological effects. Given the role of the GABA B receptor in the neurobiological and pharmacological bases of alcohol use disorder, the present study investigated the effect of ISL on a series of alcohol-related behaviors in selectively bred, female Sardinian alcohol-preferring rats. Methods and results The collected results indicated that acute treatment with ISL (5-20 mg/kg, i.p.; 50-200 mg/kg, i.g.) decreased operant oral alcohol self-administration under both fixed and progressive ratio schedules of reinforcement and suppressed cue-induced reinstatement of alcohol seeking. ISL effect on alcohol self-administration was partially blocked by pretreatment with the GABA B receptor antagonist, SCH50911, and potentiated by co-administration of the positive allosteric modulator of the GABA B receptor, GS39783. Acute treatment with doses of ISL as high as 80 mg/kg (i.p.) did not alter spontaneous locomotor activity, suggestive of the specificity of ISL effects on alcohol-related behaviors. Conclusions These results confirm the ability of ISL to behave in vivo as a GABA B receptor agonist; they also indicate that ISL reproduced the suppressing effects of the prototypic GABA B receptor agonist, baclofen, on multiple alcohol-related behaviors in rodents.

Flower-like WO3-modified Vulcan carbon GDEs for photoelectro-Fenton process: Efficient ciprofloxacin degradation and mechanistic insights - João Paulo C. Moura; Vanessa S. Antonin; Caio Machado Fernandes; Aline B. Trench; Erica S. Conrado; Michell O. Almeida; Kathia M. Honorio; Renata Colombo; Rafael Sotana; Ana M.P. Neto; Mauro C. Santos (Journal of Environmental Management, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil) - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Single-cell protein meal produced from Methylovorus menthalis (Psomi™) in extruded aquafeeds for seawater phase Atlantic salmon (Salmo salar L.): Impacts on growth performance, nutrient utilization, fish health, and fillet quality - Sean M. Tibbetts; André Dumas; Van Pham Thi Ha To; Ivan Tankovski; Noppawan Chimsung; Shane J.J. Patelakis; Stefanie M. Colombo; Talia Boates; Roberto E. Armenta; Brianna Orr Stratton (Aquaculture, 2026)

Perspectives on abiotic ecosystem services provided by glacial lakes in high-mountain areas - C. Viani; N. Colombo; M. Rogora; M. Giardino; M. Freppaz; I.M. Bollati (Ecosystem Services, 2025)

Effects of two natural astaxanthin products derived from the green microalga Haematococcus lacustris on production parameters and fillet quality of Atlantic salmon (Salmo salar) - Juan A. Manríquez-Hernández; Sean M. Tibbetts; Mark D. Fast; Stacey R. Goldberg; Roumiana Stefanova; Stefanie M. Colombo (Aquaculture International, 2025)

P32-19 Absorption Test on Different Formulations of Medical Devices Containing Silver Sulfadiazine - M. Mori; D. Colombo; A. Zerboni; D. Ianev; S. Stoilova (Toxicology Letters, 2025)

P16-06 Evaluation of the Mechanism of Action and Immunomodulatory Properties of an Oral Medical Device Containing Gelatin Tannate and Tyndallized Bacteria - A. Zerboni; S. Stoilova; D. Colombo; M. Mori (Toxicology Letters, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Late-phase depolarization and repolarization abnormalities in english bulldogs with phenotypic expression of arrhythmogenic cardiomyopathy - Mara Bagardi; Manuela Perego; Fabio M. Colombo; Alessandra Maffei; Paola G. Brambilla; Michele Polli; Giorgio Camozzini; Roberto A. Santilli (Veterinary Research Communications, 2025)

Optimizing CO2 trapping in saline aquifers under geological uncertainty: A case study of the Rio Bonito Formation, Brazil - Amin Izadpanahi; Paulo Ranazzi; Richardson M. Abraham-A; Colombo Celso Gaeta Tassinari; Marcio Augusto Sampaio (Gas Science and Engineering, 2025)

Aspartic proteases from Silybum marianum: different plant-specific inserts, different destinations - M. Laura Colombo; Agustina Fernández; Constanza S. Liggieri; Pablo Tornero; Laura S. Bakás; Sandra E. Vairo-Cavalli (Planta, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Telescopic alluvial fans and pleistocene-holocene temporary lakes in the quebradas del Río Toro and Tastil (Salta, NW Argentina): main sedimentary features - F. Colombo; J. A. Salfity; M. C. Sánchez (Journal of Iberian Geology, 2025)
The Toro and Tastil Quebradas (river valleys) present different terrace-like geoforms made up of deposits of coarse-grained clastic materials. These terraces display convex-upward surfaces, a highly variable distribution, have a small lateral extension and depend on the lithology of the geological basement, which differs significantly along the quebradas . The number of terraces between one area and another indicates that these terraced geoforms should not be ascribed to one single cause, but rather to a variety of factors, i.e. local variations at base-level. The coarse-grained materials of the terraces are usually arranged in roughly horizontal layers that characterize the outcrops. These are interfingered with fine-grained mud-rich materials. The freshwater gastropod remains in the mud-rich materials indicate that they accumulated in lacustrine-like sedimentary environments. These developed from alluvial fans that spread out from the lateral quebradas to occupy the entire main valley (q uebrada) , giving rise to natural dams and temporary lakes upstream. Absolute data obtained by radiocarbon ( 14 C) methods strongly suggest that the alluvial fans were coeval with the temporary lakes in the Upper Pleistocene - Middle Holocene. The El Niño Southern Oscillation (ENSO) effects could have brought about the local variations in base-level that generated the younger temporary lakes, whereas the older ones were probably controlled by precession cycles (at about 21,000 y). The large number of temporary lakes scattered across the region suggests the overlapping of forcing factors at local and regional scales.

Feeding ontogeny and trophic ecology of the shortfin mako shark, Isurus oxyrinchus, on the west coast of Baja California Sur, Mexico - Paula M. Velasco-Tarelo; Felipe Galván-Magaña; Colombo Estupiñán-Montaño (Regional Studies in Marine Science, 2024)

Paint particle pollution in aquatic environments: Current advances and analytical challenges - A.D. Forero-López; C.V. Colombo; A.P. Loperena; N.G. Morales-Pontet; A.C. Ronda; I.L. Lehr; G.E. De-la-Torre; M. Ben-Haddad; T.A. Aragaw; G. Suaria; G.N. Rimondino; F.E. Malanca; et al. (Journal of Hazardous Materials, 2024)

Factors controlling the water quality of rock glacier springs in European and American mountain ranges - Stefano Brighenti; Nicola Colombo; Thomas Wagner; Michael Pettauer; Nicolas Guyennon; Karl Krainer; Monica Tolotti; Michela Rogora; Luca Paro; Sandra M. Steingruber; Chantal Del Siro; Cristian Scapozza; et al. (Science of The Total Environment, 2024)

Has climate change over the last ten years caused a banalisation of diatom communities in Cypriot streams? - Marco Cantonati; David G. Armanini; Daniele Demartini; Athina Papatheodoulou; Olena P. Bilous; Federica Colombo; Nicola Angeli; Rosalina Stancheva; Gerald Dörflinger; Kalina M. Manoylov (Science of The Total Environment, 2024)

LP-38 DockTox: a molecular docking platform for screening small molecules targeting Molecular Initiating Events (MIEs) relevant to liver, kidney and brain adverse events - R. Ortega Vallbona; D. Talavera Cortés; L.E. Carpio Mulas; E. Colombo; A. Roncaglioni; M. Garcia de Lomana; E. Benfenati; D. Gadaleta; R. Gozalbes; E. Serrano Candelas (Toxicology Letters, 2024)

Retrieval of snow liquid water content from radiative transfer model, field data and PRISMA satellite data - C. Ravasio; R. Garzonio; B. Di Mauro; E. Matta; C. Giardino; M. Pepe; E. Cremonese; P. Pogliotti; C. Marin; R. Colombo (Remote Sensing of Environment, 2024)

An aquaculture risk model to understand the causes and consequences of Atlantic Salmon mass mortality events: A review - Zaman Sajid; A. Kurt Gamperl; Christopher C. Parrish; Stefanie M. Colombo; Javier Santander; Charles Mather; Barbara Neis; Ingunn Marie Holmen; Ramón Filgueira; Cynthia H. McKenzie; Lissandra Souto Cavalli; Mohamed Jeebhay; et al. (Reviews in Aquaculture, 2024)
Mass mortality events (MMEs) are defined as the death of large numbers of fish over a short period of time. These events can result in catastrophic losses to the Atlantic salmon aquaculture industry and the local economy. However, they are challenging to understand because of their relative infrequency and the high number of potential factors involved. As a result, the causes and consequences of MMEs in Atlantic salmon aquaculture are not well understood. In this study, we developed a structural network of causal risk factors for MMEs for aquaculture and the communities that depend on Atlantic salmon aquaculture. Using the Interpretive Structural Modeling (ISM) technique, we analysed the causes of Atlantic salmon mass mortalities due to environmental (abiotic), biological (biotic) and nutritional risk factors. The consequences of MMEs were also assessed for the occupational health and safety of aquaculture workers and their implications for the livelihoods of local communities. This structural network deepens our understanding of MMEs and points to management actions and interventions that can help mitigate mass mortalities. MMEs are typically not the result of a single risk factor but are caused by the systematic interaction of risk factors related to the environment, fish diseases, feeding/nutrition and cage‐site management. Results also indicate that considerations of health and safety risk, through pre‐ and post‐event risk assessments, may help to minimize workplace injuries and eliminate potential risks of human fatalities. Company and government‐assisted socio‐economic measures could help mitigate post‐mass mortality impacts. Appropriate and timely management actions may help reduce MMEs at Atlantic salmon cage sites and minimize the physical and social vulnerabilities of workers and local communities.

Monitoring Photo-Fenton and Photo-Electro-Fenton process of contaminants emerging concern by a gas diffusion electrode using Ca10-xFex-yWy(PO4)6(OH)2 nanoparticles as heterogeneous catalyst - Fausto E.B. Júnior; Beatriz T. Marin; Leticia Mira; Carlos H.M. Fernandes; Guilherme V. Fortunato; Michell O. Almeida; Kathia M. Honório; Renata Colombo; Abner de Siervo; Marcos R.V. Lanza; Willyam R.P. Barros (Chemosphere, 2024)

Characterization of artificial rainfall produced by a portable rainfall simulator using a rotating dynamic rainfall gauge system - Antônio Reynaldo de Sousa Costa; Lívia Alves Alvarenga; Michael Silveira Thebaldi; Luiz Antonio Lima; Alberto Colombo; Daniel Green; Jorge M. G. P. Isidoro (Hydrological Sciences Journal, 2024)

Zircon U-Pb and Lu-Hf isotopes reveal the crustal evolution of the SW Angolan Shield (Congo Craton) - Ezequiel Ferreira; Jérémie Lehmann; José Feliciano Rodrigues; Ben Hayes; Enrique Merino-Martínez; Lorenzo Milani; Grant M. Bybee; Trishya M. Owen‑Smith; José Luis García-Lobón; Colombo C. G. Tassinari; Henriette Ueckermann; Kei Sato; et al. (Gondwana Research, 2024)

Omega‐3 long‐chain polyunsaturated fatty acids in Atlantic salmon: Functions, requirements, sources, de novo biosynthesis and selective breeding strategies - Zeyu Zhang; Younes Miar; David Huyben; Stefanie M. Colombo (Reviews in Aquaculture, 2024)
The aquaculture industry is a substantial user of wild‐sourced fish oil to supply omega‐3 (n‐3) long‐chain polyunsaturated fatty acids (LC‐PUFAs) in fish diets, which are required by many economically important farmed fish species, particularly Atlantic salmon ( Salmo salar L.). Fish oil is commonly replaced with plant‐based oils as more environmentally and economically sustainable substitutes due to concerns regarding over‐fishing of wild stocks and increasing demand. One potential strategy to meet the physiological requirement for n‐3 LC‐PUFA is to improve n‐3 LC‐PUFA biosynthesis in salmon through selective breeding and strain enhancement. The objective of this review is to discuss strategies to supply sufficient levels of n‐3 LC‐PUFA to Atlantic salmon through the diet and de novo biosynthesis through selective breeding and salmon strain enhancement. This review provides an overview on the functions of n‐3 LC‐PUFA in Atlantic salmon, dietary requirements, source and supply of n‐3 LC‐PUFA in aquaculture feeds, and biosynthesis of n‐3 LC‐PUFA in fish. Several relevant studies have revealed the genetic influences on n‐3 LC‐PUFA biosynthesis and storage in Atlantic salmon. The results of the present review show that selective breeding of high n‐3 PUFA‐producing Atlantic salmon could be an effective strategy to improve the amount of EPA and DHA stored in tissues and reduce reliance on dietary sources of n‐3 LC‐PUFA such as fish oil.

When another one bites the dust: Environmental impact of global copper demand on local communities in the Atacama mining hotspot as registered by tree rings - Nicolás C. Zanetta-Colombo; Tobias Scharnweber; Duncan A. Christie; Carlos A. Manzano; Mario Blersch; Eugenia M. Gayo; Ariel A. Muñoz; Zoë L. Fleming; Marcus Nüsser (Science of The Total Environment, 2024)

The bimodal Fii-A2-type and calc-alkaline volcanic sequence of the Aljustrel brownfield region, Iberian Pyrite Belt, SW Iberian Massif - João Lains Amaral; Ana Rita Solá; Telmo M. Bento dos Santos; Lorena Feitoza; Colombo Tassinari; Lourenço Crispim; Martim Chichorro; Mandy Zieger-Hofmann; Jessica Gärtner; Ulf Linnemann; João Gonçalves (Geochemistry, 2024)

Masticatory Muscles Activation and TMJ Space During Asymmetrically Loaded Jaw Closing - Lea Angst; Jan Harm Koolstra; Daniel Wiedemeier; Rachel M. Van Sluijs; Anina M. Pulfer; Luigi M. Gallo; Vera Colombo (Annals of Biomedical Engineering, 2024)
Masticatory muscle activation and temporomandibular joint (TMJ) load generated during asymmetrically loaded jaw closing are largely unknown. Two different strategies were developed to explain how the central nervous system (CNS) generates muscle activation patterns during motion: minimization of joint load (MJL) vs. minimization of muscle effort (MME). The aim of the present study was to investigate, experimentally, the neuromuscular strategy selected by the CNS to coordinate jaw closing in reaction to the application of an external asymmetric load. Masticatory muscle activation was measured with electromyography (EMG) and the minimum intra-articular distance (MID) was assessed by dynamic stereometry to infer joint loading. Ten healthy subjects performed jaw-closing movements against an asymmetric mandibular load set from 0.0 to 2.0 kg in 0.5-kg steps. Recordings were analyzed by exploratory and graphical statistical tools. Moreover, the observed differences in MID and EMG among the various mandibular loads were tested using non-parametric tests for repeated measures data. The ipsilateral-contralateral differences in MID and EMG of the anterior temporalis showed a significant increase ( p p = 0.01) with increasing asymmetrical load with both joints being most heavily loaded at 1 kg. EMG signals of the masseter did not change significantly with increasing load. This study is the first to have analyzed the changes in the TMJ intra-articular space during asymmetrically loaded jaw-closing movements, not only three dimensionally and dynamically, but also combined with EMG. Asymmetrical load affected the TMJ space and masticatory muscle activation patterns, primarily resulting in an increased activation of the anterior temporalis muscle. This might suggest the involvement of a control mechanism to protect the joints from overloading. However, the results do not fully support the hypothesis of MJL nor the MME strategy.

Between family variation in EPA and DHA storage among Atlantic salmon (Salmo salar) fed a fish oil-free diet - Zeyu Zhang; Frank Powell; Andrew K. Swanson; Elizabeth Boulding; Matthew L. Rise; Younes Miar; Marine Herlin; Stefanie M. Colombo (Aquaculture, 2024)

Albinism in the Galapagos Shark, Carcharhinus Galapagensis (Snodgrass & Heller, 1905) at Malpelo Island, Colombia - Colombo Estupiñán-Montaño; Paola M. Sánchez-Gómez; Jaime O. López-Montoya (Thalassas: An International Journal of Marine Sciences, 2024)

High-Resolution In Situ Characterization of the Hydrochemical Variability Along the Fluvio-marine Transition of the Río de la Plata Estuary, Argentina - S. Heguilor; E. D. Speranza; L. M. Tatone; C. N. Skorupka; M. C. Migoya; J. C. Colombo (Estuaries and Coasts, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

P25-21: Approach and challenges in the toxicological and allergenicity risk assessment of novel proteins and their sources - I. Nuin Garciarena; O. Albert; P. Colombo; A. Fernández Dumont; M. Laganaro; A. Muñoz González; E. Noriega Fernández; G. Precup; R. Roldán Torres; A. Rossi; E. Ververis; A. Germini; et al. (Toxicology Letters, 2023)

OS04-02: Next Generation PBK modeling with PK-Sim for the prediction of chemical distribution in humans - R. Geci; D. Gadaleta; S. Proença; E. Colombo; M. García de Lomana; R. Ortega Vallbona; N. Kramer; A. Paini; L. Küpfer; S. Schaller (Toxicology Letters, 2023)

Modeling the compressive strength of metakaolin-based geopolymers based on the statistical analysis of experimental data - M. Muracchioli; G. Menardi; M. D' Agostini; G. Franchin; P. Colombo (Applied Clay Science, 2023)

The impact of Li-bearing pegmatite mining on the dissolved geochemical signature of a mountain stream in the Pampean ranges, Central Argentina - Milagros Marqués; Andrea I. Pasquini; María Gabriela García; Verena A. Campodonico; Fernando Colombo; Diego M. Gaiero; Karina L. Lecomte (Sustainable Water Resources Management, 2023)

Study of the mechanical properties of thermoplastic polyurethane (TPU) recycled from end-of-life ski-boots and techno-economic analysis (TEA) of the mechanical recycling processes - A. Nanni; L. Crosetta; G. La Fauci; F. Biagi; M. Parisi; D. Colombo; M. Colonna (Sustainable Chemistry and Pharmacy, 2023)

Hydrological, thermal and chemical influence of an intact rock glacier discharge on mountain stream water - F. Bearzot; N. Colombo; E. Cremonese; U. Morra di Cella; E. Drigo; M. Caschetto; S. Basiricò; G.B. Crosta; P. Frattini; M. Freppaz; P. Pogliotti; F. Salerno; et al. (Science of The Total Environment, 2023)

Colostrum quality associations with passive immunity transfer in foals - H B Magalhães; G Araujo; I Colombo; K M Spencer; G Podico; I F Canisso (Journal of Equine Veterinary Science, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Identification of IPT9 in Brachiaria brizantha (syn. Urochloa brizantha) and expression analyses during ovule development in sexual and apomictic plants - Luciana G. Ferreira; Diva M. A. Dusi; André S. T. Irsigler; Ana C. M. M. Gomes; Lilian H. Florentino; Marta A. Mendes; Lucia Colombo; Vera T. C. Carneiro (Molecular Biology Reports, 2023)
Background In Brachiaria sexual reproduction, during ovule development, a nucellar cell differentiates into a megaspore mother cell (MMC) that, through meiosis and mitosis, gives rise to a reduced embryo sac. In aposporic apomictic Brachiaria , next to the MMC, other nucellar cells differentiate into aposporic initials that enter mitosis directly forming an unreduced embryo sac. The IPT (isopentenyltransferase) family comprises key genes in the cytokinin (CK) pathway which are expressed in Arabidopsis during ovule development. BbrizIPT9 , a B. brizantha ( syn. Urochloa brizantha ) IPT9 gene, highly similar to genes of other Poaceae plants, also shows similarity with Arabidopsis IPT9, AtIPT9 . In this work, we aimed to investigate association of BbrizIPT9 with ovule development in sexual and apomictic plants. Methods and results RT-qPCR showed higher BbrizIPT9 expression in the ovaries of sexual than in the apomictic B. brizantha . Results of in-situ hybridization showed strong signal of BbrizIPT9 in the MMC of both plants, at the onset of megasporogenesis. By analyzing AtIPT9 knockdown mutants, we verified enlarged nucellar cell, next to the MMC, in a percentage significantly higher than in the wild type, suggesting that knockout of AtIPT9 gene triggered the differentiation of extra MMC-like cells. Conclusions Our results indicate that AtIPT9 might be involved in the proper differentiation of a single MMC during ovule development. The expression of a BbrizIPT9 , localized in male and female sporocytes, and lower in apomicts than in sexuals, and effect of IPT9 knockout in Arabidopsis, suggest involvement of IPT9 in early ovule development.

Towards achieving circularity and sustainability in feeds for farmed blue foods - Stefanie M. Colombo; Koushik Roy; Jan Mraz; Alex H. L. Wan; Simon J. Davies; Sean M. Tibbetts; Margareth Øverland; David S. Francis; Melissa M. Rocker; Laura Gasco; Emma Spencer; Marc Metian; et al. (Reviews in Aquaculture, 2023)
The aims of this review are to describe the role of ‘blue‐food production’ (animals, plants and algae harvested from freshwater and marine environments) within a circular bioeconomy, discuss how such a framework can help the sustainability and resilience of aquaculture and to summarise key examples of novel nutrient sources that are emerging in the field of fed‐aquaculture species. Aquaculture now provides >50% of the global seafood supply, a share that is expected to increase to at least 60% within the next decade. Aquaculture is an important tool for reducing resource consumption in global protein production and increasing resilience to climate change and other global disruptions (i.e. pandemics, geo‐political instability). Importantly, blue foods also provide essential nutrition for a growing human population. Blue foods are helping to help the global goal of ‘zero hunger’ (United Nation's Sustainable Development Goal 2) while reducing the dependency on finite natural resources but further refinement and new solutions are needed to make the industry more ‘circular’ and sustainable, particularly with respect to sourcing raw materials for aquafeeds. This review describes the feed resources that are available or may be created within a circular bioeconomy framework, their role within the framework and in aquaculture and ultimately, how these resources contribute to de‐risking and establishing a resilient aquaculture production chain.

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Atlantic salmon adapt to low dietary n-3 PUFA and warmer water temperatures by increasing feed intake and expression of n-3 biosynthesis-related transcripts - Stefanie M. Colombo; Suzanne M. Budge; Jennifer R. Hall; Jovana Kornicer; Nolan White (Fish Physiology and Biochemistry, 2023)

Exploratory analysis on Canadian consumer perceptions, habits, and opinions on salmon consumption and production in Canada - Angelisa T. Y. Osmond; Sylvain Charlebois; Stefanie M. Colombo (Aquaculture International, 2023)

Morphotypes of Ciborinia camelliae Kohn infecting camellias in Italy - Marco Saracchi; Elena M. Colombo; Dario Locati; Irene Valenti; Andrea Corneo; Paolo Cortesi; Andrea Kunova; Matias Pasquali (Journal of Plant Pathology, 2022)

Population growth dynamics and their implications for fish welfare in mixed-size cohorts of Cyprinus Carpio var koi grown in a commercial-scale aquaponics system - Danielle M. Maitland; Joe Baker; Greg Chambers; Neil W. Ross; Stefanie M. Colombo (Aquaculture International, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Nanopore Genome Sequencing and Variant Analysis of the Susceptible Candida auris Strain L1537/2020, Salvador, Brazil - Auke W. de Jong; Elaine C. Francisco; João Nóbrega de Almeida; Igor B. Brandão; Felicidade M. Pereira; Pedro H. Presta Dias; Magda M. de Miranda Costa; Regiane T. de Souza Jordão; Duong Vu; Arnaldo L. Colombo; Ferry Hagen (Mycopathologia, 2021)
Candida auris has been reported worldwide, but only in December 2020, the first strain from a COVID-19 patient in Brazil was isolated. Here, we describe the genome sequence of this susceptible C. auris strain and performed variant analysis of the genetic relatedness with strains from other geographic localities.

Analgesic properties of a food grade lecithin delivery system of Zingiber officinale and Acmella oleracea standardized extracts in rats - Carla Lobina; Roberta Sau; Federica Fara; Paola Maccioni; Mauro A. M. Carai; Giancarlo Colombo (Natural Product Research, 2021)

In-Stent Restenosis Progression in Human Superficial Femoral Arteries: Dynamics of Lumen Remodeling and Impact of Local Hemodynamics - Monika Colombo; Yong He; Anna Corti; Diego Gallo; Federica Ninno; Stefano Casarin; Jared M Rozowsky; Francesco Migliavacca; Scott Berceli; Claudio Chiastra (Annals of Biomedical Engineering, 2021)
In-stent restenosis (ISR) represents a major drawback of stented superficial femoral arteries (SFAs). Motivated by the high incidence and limited knowledge of ISR onset and development in human SFAs, this study aims to (i) analyze the lumen remodeling trajectory over 1-year follow-up period in human stented SFAs and (ii) investigate the impact of altered hemodynamics on ISR initiation and progression. Ten SFA lesions were reconstructed at four follow-ups from computed tomography to quantify the lumen area change occurring within 1-year post-intervention. Patient-specific computational fluid dynamics simulations were performed at each follow-up to relate wall shear stress (WSS) based descriptors with lumen remodeling. The largest lumen remodeling was found in the first post-operative month, with slight regional-specific differences (larger inward remodeling in the fringe segments, p

Molecular Identification and Antimicrobial Activity of Foliar Endophytic Fungi on the Brazilian Pepper Tree (Schinus terebinthifolius) Reveal New Species of Diaporthe - Germana D. dos Santos; Renata R. Gomes; Rosana Gonçalves; Gheniffer Fornari; Beatriz H. L. N. S. Maia; Claudia Schmidt-Dannert; Francois Gaascht; Chirlei Glienke; Gabriela X. Schneider; Israella R. Colombo; Juliana Degenhardt-Goldbach; João L. M. Pietsch; et al. (Current Microbiology, 2021)

Freshwater, Landlocked Grand Lake Strain of Atlantic Salmon (Salmo salar L.) as a Potential Genetic Source of Long Chain Polyunsaturated Fatty Acids Synthesis - Stefanie M. Colombo; Mohamed Emam; Brian C. Peterson; Jennifer R. Hall; Gary Burr; Zeyu Zhang; Matthew L. Rise (Frontiers in Marine Science, 2021)
Selection efforts focused on adaptation to plant-based diets, particularly the ability to synthesize polyunsaturated fatty acids (PUFA), are now emerging in aquaculture. Landlocked salmon (Grand Lake population; GL) may differ from the commercial Saint John River (SJR) strain in terms of PUFA metabolism. The objective of this study was to determine if GL salmon can contribute toward broodstock selection for enhanced PUFA synthesis. Two diets containing either fish oil (FO) or plant-based oil (FO-free) were fed to the SJR and GL strains (∼58 g/fish) for 16 weeks. Growth, liver, and muscle fatty acid (FA) content, and transcript expression of lipid metabolism and inflammation-related genes were evaluated. GL salmon fed the FO diet showed reduced growth compared to SJR salmon (fed either diet); however, GL salmon fed the FO-free diet, growth was not significantly different compared to any group. In liver, SJR salmon fed the FO-free diet had higher levels of n-6 PUFAs (21.9%) compared to GL fed the same diet (15.9%); while GL salmon fed the FO-free diet had higher levels of monounsaturated FAs (48.9%) compared with SJR salmon fed the same diet (35.7%). 20:5n-3 and 22:6n-3 were the same in GL and SJR salmon liver and muscle, respectively, fed the FO-free diet. In liver, GL salmon fed the FO-free diet had higher acac and acly compared to all treatments and had higher fasb compared to both strains fed the FO-diet. GL salmon fed the FO-free diet had higher cd36c and fabp3b in liver compared to GL salmon fed the FO diet and SJR salmon fed either diet. GL salmon fed the FO-free diet had higher lect2a and pgds in liver compared to SJR salmon fed the FO-free diet. In muscle, GL salmon fed the FO-free diet had higher fadsd5 and fadsd6b compared with both strains fed the FO diet. These results suggest there is a genetic basis behind the potential for GL salmon to utilize FO-free diets more efficiently than SJR salmon, with regards to FA metabolism.

‘Aquafeed 3.0’: creating a more resilient aquaculture industry with a circular bioeconomy framework - Stefanie M. Colombo; Giovanni M. Turchini (Reviews in Aquaculture, 2021)

The use of biomimetic tools for water quality monitoring: passive samplers versus sentinel organisms - M. Morrone; N. E. Cappelletti; L. M. Tatone; M. J. Astoviza; J. C. Colombo (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Zootechnical performance, biochemical response, and chromaticity in Pacific white shrimp (Litopenaeus vannamei) (Boone, 1931) after the inclusion of lyophilized açaí (Euterpe oleracea) in the diet - Shadai M. Silva; Patricia B. Ramos; Juan R. Buitrago; Thamyres V. N. da Silva; Cleber S. Simião; Grecica M. Colombo; Marcos Schmitz; Marcelo B. Tesser; Carlos Prentice; Wilson Wasielesky; José M. Monserrat (Aquaculture International, 2020)

Projected declines in global DHA availability for human consumption as a result of global warming - Stefanie M. Colombo; Timothy F. M. Rodgers; Miriam L. Diamond; Richard P. Bazinet; Michael T. Arts (Ambio, 2020)
Docosahexaenoic acid (DHA) is an essential, omega-3, long-chain polyunsaturated fatty acid that is a key component of cell membranes and plays a vital role in vertebrate brain function. The capacity to synthesize DHA is limited in mammals, despite its critical role in neurological development and health. For humans, DHA is most commonly obtained by eating fish. Global warming is predicted to reduce the de novo synthesis of DHA by algae, at the base of aquatic food chains, and which is expected to reduce DHA transferred to fish. We estimated the global quantity of DHA (total and per capita) currently available from commercial (wild caught and aquaculture) and recreational fisheries. The potential decrease in the amount of DHA available from fish for human consumption was modeled using the predicted effect of established global warming scenarios on algal DHA production and ensuing transfer to fish. We conclude that an increase in water temperature could result, depending on the climate scenario and location, in a ~ 10 to 58% loss of globally available DHA by 2100, potentially limiting the availability of this critical nutrient to humans. Inland waters show the greatest potential for climate-warming-induced decreases in DHA available for human consumption. The projected decrease in DHA availability as a result of global warming would disproportionately affect vulnerable populations (e.g., fetuses, infants), especially in inland Africa (due to low reported per capita DHA availability). We estimated, in the worst-case scenario, that DHA availability could decline to levels where 96% of the global population may not have access to sufficient DHA.

Radiotherapy-induced malignancies in breast cancer patients with TP53 pathogenic germline variants (Li–Fraumeni syndrome) - Vanessa Petry; Renata Colombo Bonadio; Allyne Queiroz Carneiro Cagnacci; Luiz Antonio Leite Senna; Roberta do Nascimento Galvão Campos; Guilherme Cutait Cotti; Paulo M. Hoff; Maria Candida Barisson Villares Fragoso; Maria del Pilar Estevez-Diz (Familial Cancer, 2020)

Coupled Modeling of Sedimentary Basin and Geomechanics: A Modified Drucker–Prager Cap Model to Describe Rock Compaction in Tectonic Context - N. Guy; D. Colombo; J. Frey; T. Cornu; M. C. Cacas-Stentz (Rock Mechanics and Rock Engineering, 2019)

A novel in vitro methodology to cultivate arbuscular mycorrhizal fungi combining soil and synthetic media - V. A. Silvani; M. Statello; M. V. Scorza; M. Pérgola; R. P. Colombo; A. M. Godeas (Symbiosis, 2019)

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

Elucidating the symbiotic interactions between a locally isolated microalga Chlorella vulgaris and its co-occurring bacterium Rhizobium sp. in synthetic municipal wastewater - L. Ferro; M. Colombo; E. Posadas; C. Funk; R. Muñoz (Journal of Applied Phycology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Short-Term Effects of Genetically Modified Potato on Arbuscular Mycorrhizal Fungal Communities - Betina I. Stephan; Roxana P. Colombo; Vanesa A. Silvani; Mariana Pérgola; Alicia M. Godeas; Alejandro G. Pardo; Laura Fernández Bidondo (Journal of Soil Science and Plant Nutrition, 2019)

In Situ Tissue Labeling of Cerebral Amyloid Using HIV-Related Tat Peptide - E. Maderna; L. Colombo; A. Cagnotto; G. Di Fede; A. Indaco; F. Tagliavini; M. Salmona; G. Giaccone (Molecular Neurobiology, 2018)

Nanoemulsion-Loaded Hydrogels for Topical Administration of Pentyl Gallate - Regina G. Kelmann; Mariana Colombo; Ricardo J. Nunes; Cláudia M. O. Simões; Letícia S. Koester (AAPS PharmSciTech, 2018)

Promising primers for detection of phytoplasma causing coconut lethal yellowing disease in Mozambique - M. O. M. Mazivele; Valter Nuaila; M. Durante; M. M. Colombo; E. Taviani (Phytoparasitica, 2018)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

Histamine food poisonings: A systematic review and meta-analysis - Fabio M. Colombo; Patrizia Cattaneo; Enrica Confalonieri; Cristian Bernardi (Critical Reviews in Food Science and Nutrition, 2018)

Ambrosia pollen source inventory for Italy: a multi-purpose tool to assess the impact of the ragweed leaf beetle (Ophraella communa LeSage) on populations of its host plant - M. Bonini; Branko Šikoparija; C. A. Skjøth; G. Cislaghi; P. Colombo; C. Testoni; M. Smith (International Journal of Biometeorology, 2018)

Suppressing effect of COR659 on alcohol, sucrose, and chocolate self-administration in rats: involvement of the GABAB and cannabinoid CB1 receptors - Paola Maccioni; Giancarlo Colombo; Irene Lorrai; Alessandro Zaru; Mauro A. M. Carai; Gian Luigi Gessa; Antonella Brizzi; Claudia Mugnaini; Federico Corelli (Psychopharmacology, 2017)

Beneficial and Safety Properties of a Corynebacterium vitaeruminis Strain Isolated from the Cow Rumen - M. Colombo; N. P. A. Castilho; S. D. Todorov; L. A. Nero (Probiotics and Antimicrobial Proteins, 2017)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

Uncertainty quantification of overpressure buildup through inverse modeling of compaction processes in sedimentary basins - Ivo Colombo; Giovanni M. Porta; Paolo Ruffo; Alberto Guadagnini (Hydrogeology Journal, 2017)

Healthy and tumoral tissue resistivity in wild-type and sparc–/– animal models - D. Meroni; G. Mauri; D. Bovio; A. M. Bianchi; C. Chiodoni; M. P. Colombo; E. Meroni; A. Aliverti (Medical & Biological Engineering & Computing, 2016)

Fatty acid alterations in the detritivorous Prochilodus lineatus promoted by opportunistic feeding on sewage discharges in the R ío de la P lata estuary - E. D. Speranza; M. Colombo; L. M. Tatone; N. Cappelletti; M. C. Migoya; J. C. Colombo (Journal of Fish Biology, 2016)
Muscle fatty acid profiles and PCB contents of the detritivorous species Prochilodus lineatus and its diet (stomach contents, settling particles and sediments) were analysed from reference and polluted areas of the Paraná‐Rio de la Plata basin, to evaluate the alterations produced by opportunistic feeding on sewage discharges. Overall muscle fatty acid composition was dominated by saturated and monounsaturated 16 and 18 carbon (18 C‐ FA ) components with reduced long‐chain polyunsaturated fatty acids ( LC‐PUFA ). Compared to sediments, settling particles and stomach contents were enriched in lipids and had a similar fatty acid composition. Opportunistic feeding on sewage detritus at Buenos Aires resulted in enhanced PCB and triglyceride accumulation, with higher proportions of 18 C‐ FA and lower proportions of 16:1 and LC‐PUFA compared to fish from northern pristine reaches of the basin. Mid‐Paraná showed intermediate values reflecting mixing of the North stock with migrating Buenos Aires P. lineatus identified by their lipid and contaminant profile. According to multivariate analyses, this geographical variation of fatty acid composition was strongly influenced by PCB concentration. Prochilodus lineatus assimilates the energy subsidy of sewage inputs through enhanced lipogenesis with dominant 18 C‐ FA and significant amounts of valuable LC‐PUFA . This lipid alteration facilitates the bioaccumulation of PCBs which in turn may reinforce the adipogenic effect of sewage feeding.

Paediatric nasopharyngeal cytology: a new diagnostic opportunity? - S. Torretta; P. Marchisio; M. R. Colombo; C. Rosazza; L. Pignataro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Stem Cell Factor (SCF) is a putative biomarker of antidepressant response - Francesco Benedetti; Sara Poletti; Thomas A. Hoogenboezem; Clara Locatelli; Oliver Ambrée; Harm de Wit; Annemarie J. M. Wijkhuijs; Elena Mazza; Chiara Bulgarelli; Benedetta Vai; Cristina Colombo; Enrico Smeraldi; et al. (Journal of Neuroimmune Pharmacology, 2016)

A follow-up study examining airborne Ambrosia pollen in the Milan area in 2014 in relation to the accidental introduction of the ragweed leaf beetle Ophraella communa - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; Ł. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2016)

Properties and Mechanobiological Behavior of Bovine Nasal Septum Cartilage - Maria Rita Correro-Shahgaldian; Jasmin Introvigne; Chafik Ghayor; Franz E. Weber; Luigi M. Gallo; Vera Colombo (Annals of Biomedical Engineering, 2016)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Botanicals authentication in food, food supplements and herbal medicinal products - M. L. Colombo (Plant Biosystems, 2016)

Biological Effects of Simvastatin Formulated as pMDI on Pulmonary Epithelial Cells - Alaa S. Tulbah; Hui Xin Ong; Wing-Hin Lee; Paolo Colombo; Paul M. Young; Daniela Traini (Pharmaceutical Research, 2016)

Is the recent decrease in airborne Ambrosia pollen in the Milan area due to the accidental introduction of the ragweed leaf beetle Ophraella communa? - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; L. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2015)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Continuous streamflow simulation for index flood estimation in an Alpine basin of northern Italy - G. Ravazzani; D. Bocchiola; B. Groppelli; A. Soncini; M.C. Rulli; F. Colombo; M. Mancini; R. Rosso (Hydrological Sciences Journal, 2015)

Seasonal and inter-annual variability of water quality in the Uruguay River, Argentina - Juan C. Colombo; Carlos N. Skorupka; Claudio Bilos; Leandro Tatone; Natalia Cappelletti; M. Carolina Migoya; Malena Astoviza; Eric Speranza (Hydrological Sciences Journal, 2015)

Immunomodulatory Effects of a Low-Dose Clarithromycin-Based Macrolide Solution Pressurised Metered Dose Inhaler - Mehra Haghi; Alessandro Saadat; Bing Zhu; Gaia Colombo; Gregory King; Paul M. Young; Daniela Traini (Pharmaceutical Research, 2015)

Bioaccumulation of dioxin-like PCBs and PBDEs by detritus-feeding fish in the Rio de la Plata estuary, Argentina - N. Cappelletti; E. Speranza; L. Tatone; M. Astoviza; M. C. Migoya; J. C. Colombo (Environmental Science and Pollution Research, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Combined effects of arbuscular mycorrhizal fungi and exogenous cytokinins on pomegranate (Punica granatum) under two contrasting water availability conditions - M. J. Bompadre; L. Fernández Bidondo; V. A. Silvani; R. P. Colombo; M. Pérgola; A. G. Pardo; A. M. Godeas (Symbiosis, 2015)

Performance of Bemisia tabaci (Genn.) Biotype B (Hemiptera: Aleyrodidae) on Weeds - L D M Sottoriva; A L Lourenção; C A Colombo (Neotropical Entomology, 2014)

Behavior of Dioxin Like PCBs and PBDEs During Early Diagenesis of Organic Matter in Settling Material and Bottom Sediments from the Sewage Impacted Buenos Aires’ Coastal Area, Argentina - N. Cappelletti; C. N. Skorupka; M. C. Migoya; L. Tatone; M. Astoviza; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2014)

Novel Simvastatin Inhalation Formulation and Characterisation - Alaa S. Tulbah; Hui Xin Ong; Paolo Colombo; Paul M. Young; Daniela Traini (AAPS PharmSciTech, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Trends in Surface Water Chemistry in Acidified Areas in Europe and North America from 1990 to 2008 - Øyvind A. Garmo; Brit Lisa Skjelkvåle; Heleen A. de Wit; Luca Colombo; Chris Curtis; Jens Fölster; Andreas Hoffmann; Jakub Hruška; Tore Høgåsen; Dean S. Jeffries; W. Bill Keller; Pavel Krám; et al. (Water, Air, & Soil Pollution, 2014)

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

Seasonal course of photosynthetic efficiency in Larix decidua Mill. in response to temperature and change in pigment composition during senescence - M. Galvagno; M. Rossini; M. Migliavacca; E. Cremonese; R. Colombo; U. Morra di Cella (International Journal of Biometeorology, 2013)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

Presence of pathogenic Vibrio Parahaemolyticus in waters and seafood from the Tunisian Sea - Sadok Khouadja; Elisabetta Suffredini; Matteo Spagnoletti; Luciana Croci; Mauro M. Colombo; Bakhrouf Amina (World Journal of Microbiology and Biotechnology, 2013)

Molecular Identification of Melanised Non-Sporulating Moulds: A Useful Tool for Studying the Epidemiology of Phaeohyphomycosis - Daniel W. C. L. Santos; Ana Carolina B. Padovan; Analy S. A. Melo; Sarah S. Gonçalves; Viviane R. Azevedo; Marilia M. Ogawa; Tainá Veras Sandes Freitas; Arnaldo L. Colombo (Mycopathologia, 2013)

Trace Metals in Settling Particles from the Sewage Impacted Buenos Aires Coastal Area in the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2013)

The ecological and genetic basis of convergent thick‐lipped phenotypes in cichlid fishes - Marco Colombo; Eveline T. Diepeveen; Moritz Muschick; M. EMILIA Santos; Adrian Indermaur; Nicolas Boileau; Marta Barluenga; Walter Salzburger (Molecular Ecology, 2013)
The evolution of convergent phenotypes is one of the most interesting outcomes of replicate adaptive radiations. Remarkable cases of convergence involve the thick‐lipped phenotype found across cichlid species flocks in the E ast A frican G reat L akes. Unlike most other convergent forms in cichlids, which are restricted to E ast A frica, the thick‐lipped phenotype also occurs elsewhere, for example in the C entral A merican M idas C ichlid assemblage. Here, we use an ecological genomic approach to study the function, the evolution and the genetic basis of this phenotype in two independent cichlid adaptive radiations on two continents. We applied phylogenetic, demographic, geometric morphometric and stomach content analyses to an A frican ( L obochilotes labiatus ) and a C entral A merican ( A mphilophus labiatus ) thick‐lipped species. We found that similar morphological adaptations occur in both thick‐lipped species and that the ‘fleshy’ lips are associated with hard‐shelled prey in the form of molluscs and invertebrates. We then used comparative I llumina RNA sequencing of thick vs. normal lip tissue in E ast A frican cichlids and identified a set of 141 candidate genes that appear to be involved in the morphogenesis of this trait. A more detailed analysis of six of these genes led to three strong candidates: A ctb , C ldn7 and C opb . The function of these genes can be linked to the loose connective tissue constituting the fleshy lips. Similar trends in gene expression between A frican and C entral A merican thick‐lipped species appear to indicate that an overlapping set of genes was independently recruited to build this particular phenotype in both lineages.

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data - E. D. Speranza; N. Cappelletti; M. C. Migoya; L. M. Tatone; J. C. Colombo (Journal of Fish Biology, 2012)
This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus collected in Metropolitan Buenos Aires, the lower Paraná River (Paraná: 200–1000 km from Buenos Aires) and the middle Paraná and Paraguay Rivers (North: 1000–1400 km north). Biochemical variables and pollutants exhibited large variability [Lipids 1·1–89·5% wet mass; ALI 1·4–413; LABs not detectable (n.d.)–115·2; PCBs n.d.–27·9; OClPs n.d.–11·8 µg g −1 dry mass], due to the contrast of Buenos Aires with North fish. Fish from Buenos Aires were fatty (lipids 24·7 ± 12·3% wet mass), enriched in 18 carbon fatty acids and severely contaminated (ALI 152·4 ± 72·3; LABs 65·1 ± 26·4; PCBs 15·2 ± 6·8; OClPs 1·8 ± 1·9 µg g −1 dry mass mean ± s.d .). In contrast, fish from North were lean (4·1 ± 3·1% wet mass), enriched in long chain (>20 carbons) polyunsaturated fatty acids, with average one to two orders of magnitude lower pollutant levels (ALI 41·2 ± 51·9; PCBs 2·2 ± 3·5; LABs 8·8 ± 21·1; OClPs 0·67 ± 0·75 µg g −1 dry mass mean ± s.d .). Paraná showed intermediate values in all variables, denoting the mixing of different fish stocks. Based on principal component analysis, 14 outliers from 60 North and Paraná samples (representing 26 from 108 individual fish) were identified as pertaining to the Buenos Aires group with very similar lipid and pollutant levels. Data suggest that P. lineatus migrates a highly variable distance, exceeding 800–1000 km in multiple spatial and temporal overlapping ranges. Chemometric analysis of biochemical and pollutant data effectively discriminates fish according to the chemical signature acquired by detritus feeding in pristine and contaminated urban or industrial areas.

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Production of tannase from wood-degrading fungus using as substrate plant residues: purification and characterization - R. M. Ordoñez; I. Colombo; M. R. Alberto; M. I. Isla (World Journal of Microbiology and Biotechnology, 2011)

Pingüino In-bearing polymetallic vein deposit, Deseado Massif, Patagonia, Argentina: characteristics of mineralization and ore-forming fluids - Sebastián M. Jovic; Diego M. Guido; Isidoro B. Schalamuk; Francisco J. Ríos; Colombo C. G. Tassinari; Clemente Recio (Mineralium Deposita, 2011)

Metamorphic P-T evolution of granulites in the central Ribeira Fold Belt, SE Brazil - Telmo M. Bento dos Santos; José M. Munhá; Colombo C. G. Tassinari; Paulo E. Fonseca; Coriolano Dias Neto (Geosciences Journal, 2011)

Calcification in bleached and unbleached Montastraea faveolata: evaluating the role of oxygen and glycerol - M. F. Colombo-Pallotta; A. Rodríguez-Román; R. Iglesias-Prieto (Coral Reefs, 2010)

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Remote sensing of larch phenological cycle and analysis of relationships with climate in the Alpine region - L. BUSETTO; R. COLOMBO; M. MIGLIAVACCA; E. CREMONESE; M. MERONI; M. GALVAGNO; M. ROSSINI; C. SINISCALCO; U. MORRA DI CELLA; E. PARI (Global Change Biology, 2010)
This research aims at developing a remote sensing technique for monitoring the interannual variability of the European larch phenological cycle in the Alpine region of Aosta Valley (Northern Italy) and to evaluate its relationships with climatic factors. Phenological field observations were conducted in eight test sites from 2005 to 2007 to determine the dates of completion of different phenological phases. MODerate Resolution Imaging Spectrometer (MODIS) 250 m 16‐days normalized difference vegetation index (NDVI) time series were fitted with double logistic curves and the dates corresponding to different features of the curves were determined. Comparison with field data showed that the features of the fitted NDVI curve that allowed the best estimate of the start and end of the growing season were the zeroes of its third derivative (MAE of 6 and 4 days, respectively). The start and end of season were also estimated with the spring warming (SW) and growing season index (GSI) phenological models. MODIS start and end of season dates generally agreed with those obtained by the SW and GSI climate‐driven phenological models. However, phenological models provided erroneous results when applied in years with anomalous meteorological conditions. The relationships between interannual variability of the larch phenological cycle and climate were investigated by comparing the mean start and end of season yearly anomalies with air temperature anomalies. A strong linear relationship ( R 2 =0.91) was found between mean spring temperatures and mean start of season dates, with an increase of 1 °C in mean spring temperature leading to a 7‐day anticipation of mean larch bud‐burst date. Leaf coloring dates were found to be best related with mean September temperature ( R 2 =0.77), but with higher spring temperatures appearing to lead to earlier leaf coloring.

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis - H. M. Murray; S. P. Lall; R. Rajaselvam; L. A. Boutilier; R. M. Flight; B. Blanchard; S. Colombo; V. Mohindra; M. Yúfera; S. E. Douglas (Marine Biotechnology, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Vertical Fluxes and Accumulation of Trace Metals in Superficial Sediments of the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2009)

Pulmonary Spray Dried Powders of Tobramycin Containing Sodium Stearate to Improve Aerosolization Efficiency - Chiara Parlati; Paolo Colombo; Francesca Buttini; Paul M. Young; Handoko Adi; Alaina J. Ammit; Daniela Traini (Pharmaceutical Research, 2009)

Acoustic survey of a jellyfish-dominated ecosystem (Mljet Island, Croatia) - G. Alvarez Colombo; A. Benović; A. Malej; D. Lučić; T. Makovec; V. Onofri; M. Acha; A. Madirolas; H. Mianzan (Hydrobiologia, 2009)

Leaf level early assessment of ozone injuries by passive fluorescence and photochemical reflectance index - M. Meroni; V. Picchi; M. Rossini; S. Cogliati; C. Panigada; C. Nali; G. Lorenzini; R. Colombo (International Journal of Remote Sensing, 2008)

Update on the Genus Trichosporon - Thomas C. Chagas-Neto; Guilherme M. Chaves; Arnaldo L. Colombo (Mycopathologia, 2008)

European larch phenology in the Alps: can we grasp the role of ecological factors by combining field observations and inverse modelling? - M. Migliavacca; E. Cremonese; R. Colombo; L. Busetto; M. Galvagno; L. Ganis; M. Meroni; E. Pari; M. Rossini; C. Siniscalco; U. Morra di Cella (International Journal of Biometeorology, 2008)

Influence of vestibular and visual stimulation on split-belt walking - B. Marques; G. Colombo; R. Müller; M. R. Dürsteler; V. Dietz; D. Straumann (Experimental Brain Research, 2007)

The Cannabinoid CB1 Receptor Antagonist, Rimonabant, as a Promising Pharmacotherapy for Alcohol Dependence: Preclinical Evidence - Giancarlo Colombo; Alessandro Orrù; Paola Lai; Claudia Cabras; Paola Maccioni; Marina Rubio; Gian Luigi Gessa; Mauro A. M. Carai (Molecular Neurobiology, 2007)

Reducing effect of the positive allosteric modulator of the GABAB receptor, GS39783, on alcohol self-administration in alcohol-preferring rats - Paola Maccioni; Daniela Pes; Alessandro Orrù; Wolfgang Froestl; Gian Luigi Gessa; Mauro A. M. Carai; Giancarlo Colombo (Psychopharmacology, 2007)

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Association Between the cfxA Gene and Transposon Tn4555 in Bacteroides distasonis Strains and Other Bacteroides Species - Livia Q. Ferreira; Katia E. S. Avelar; Jessica M. B. D. Vieira; Geraldo R. de Paula; Ana P. V. Colombo; Regina M. C. P. Domingues; Maria C. S. Ferreira (Current Microbiology, 2007)

Lack of tolerance to the suppressing effect of rimonabant on chocolate intake in rats - Gian Luigi Gessa; Alessandro Orrù; Paola Lai; Paola Maccioni; Rossella Lecca; Carla Lobina; Mauro A. M. Carai; Giancarlo Colombo (Psychopharmacology, 2006)

Systematic GIS-based landslide inventory as the first step for effective landslide-hazard management - A. Colombo; L. Lanteri; M. Ramasco; C. Troisi (Landslides, 2005)

EU-OSTID: A Collection of Transposon Insertional Mutants for Functional Genomics in Rice - L. J. G van Enckevort; Gaëtan Droc; Pietro Piffanelli; Raffaella Greco; Cyril Gagneur; Christele Weber; Víctor M. González; Pere Cabot; Fabio Fornara; Stefano Berri; Berta Miro; Ping Lan; et al. (Plant Molecular Biology, 2005)

Single joint perturbation during gait: neuronal control of movement trajectory - V. Dietz; G. Colombo; R. Mller (Experimental Brain Research, 2004)

Role of GABAB receptor in alcohol dependence: Reducing effect of baclofen on alcohol intake and alcohol motivational properties in rats and amelioration of alcohol withdrawal syndrome and alcohol craving in human alcoholics - Giancarlo Colombo; Giovanni Addolorato; Roberta Agabio; Mauro A. M. Carai; Fabio Pibiri; Salvatore Serra; Giovanni Vacca; Gian Luigi Gessa (Neurotoxicity Research, 2004)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Ovule-specific MADS-box proteins have conserved protein-protein interactions in monocot and dicot plants - R. Favaro; R. Immink; V. Ferioli; B. Bernasconi; M. Byzova; G. Angenent; M. Kater; L. Colombo (Molecular Genetics and Genomics, 2002)

Risk Factors for Breakthrough Candidemia - M. Nucci; A. Colombo (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Multiple sources for ore-forming fluids in the Neves Corvo VHMS Deposit of the Iberian Pyrite Belt (Portugal): strontium, neodymium and lead isotope evidence - Jorge M. Relvas; Colombo C. Tassinari; José Munhá; Fernando J. Barriga (Mineralium Deposita, 2001)

Genomic changes in transgenic rice (Oryza sativa L.) plants produced by infecting calli with Agrobacterium tumefaciens - M. Labra; C. Savini; M. Bracale; N. Pelucchi; L. Colombo; M. Bardini; F. Sala (Plant Cell Reports, 2001)

Single-strand conformation polymorphism analysis of the glucose transporter gene GLUT1 in maturity-onset diabetes of the young - M. Baroni; F. Sentinelli; O. Massa; S. Romeo; C. Colombo; U. Di Mario; F. Barbetti (Journal of Molecular Medicine, 2001)

Feeding on survival-food: gelatinous plankton as a source of food for anchovies - H. Mianzan; M. Pájaro; G. Alvarez Colombo; A. Madirolas (Hydrobiologia, 2001)

Effects of diet supplementation with carp ovary on gonad differentiation and growth of the European eel - G. Grandi; F. Poerio; G. Colombo; M. Chicca (Journal of Fish Biology, 2000)
Treating elvers of European eel Anguilla anguilla with mature carp ovary for 3–6 months during early growth induced female differentiation in 51·6–66·7% of treated animals compared with c . 5% in controls. The treatment also induced differentiation of ovaries in eels L T and a higher number of Syrski organs with ambisexual characters, and was most effective when administered at an early growth stage. The results could be attributed to the natural steroid content of the carp ovary. The total weight of treated animals at the end of the farm experiment was 84·7% higher than controls. The specific growth rate for weight was significantly higher in female yellow eels than in males, for both control and treated groups. The enhanced growth was related to induced feminization. A diet supplementation with mature carp ovary could be a good approach to control of sex differentiation and growth in eels.

Antidepressant-like effect of ethanol revealed in the forced swimming test in Sardinian alcohol-preferring rats - Roberto Ciccocioppo; Izabela Panocka; Rino Froldi; Giancarlo Colombo; Gian Luigi Gessa; M. Massi (Psychopharmacology, 1999)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Free circulating magnesium and loop diuretics in humans - T. Gozzi; S. Dürler; A. C. Truttman; J. P. Colombo; M. G. Bianchetti (European Journal of Clinical Pharmacology, 1997)

Exopolysaccharide of Nostoc muscorum (Cyanobacteria) in the aggregation of soil particles - G. Zulpa de Caire; M. Storni de Cano; M. C. Zaccaro de Mulé; R. M. Palma; K. Colombo (Journal of Applied Phycology, 1997)

Characterization of a biofilter treating toluene contaminated air - V. Andreoni; G. Origgi; M. Colombo; E. Calcaterra; A. Colombi (Biodegradation, 1997)

G6PD Pinar del Ro: A new variant discovered in a Cuban family - R. Gonzlez; M. Wade; M. Estrada; E. Svarch; B. Colombo (Biochemical Genetics, 1977)